Widowhood and Alcohol, Tobacco, and Other Drug Use Among Older Adults in India. (24th October 2016) - Perkins, Jessica M; Lee, Hwa-Young; Lee, Jong-Koo; Heo, Jongho; Krishna, Aditi; Choi, Sugy; Nam, You-Seon; Oh, Juhwan; Subramanian, S V
Abstract: Objective: We sought to assess how widowhood among older adults in India was associated with alcohol consumption, smoking, and use of chewing tobacco or other drugs. Method: Data were collected in 2011 from 9, 852 adults aged 60 and older from seven regionally diverse states in India. Regression analyses provided estimates of the relationship between widowhood and having smoked cigarettes, consumed alcohol, or used chewed tobacco or other drugs in the past month among men, adjusting for demographic and socioeconomic factors. We also estimated the relationship between widowhood and past-month substance use among women. Results: Recently widowed men (within 0–4 years) were 1.76 times (95% confidence interval [CI] 1.01–3.09, p < .05) more likely to have consumed alcohol and 1.62 times (95% CI 1.01–2.59, p < .05) more likely to have used chewing tobacco or other drugs as compared with married men. Women widowed for any length of time were 1.37 times (95% CI 1.11–1.69, p < .01) more likely to have used chewing tobacco or other drugs. Discussion: Interventions aimed at reducing use of chewing tobacco or other drugs among older adults in India should consider focusing on recently widowed men and women widowed for any amount of time.